THE URGENCY OF REGULATION OF SIGHAT TAKLIK TALAK TO PROTECT WIVES' RIGHTS IN MARRIAGE FROM A POSITIVE LEGAL PERSPECTIVE IN INDONESIA - Febrianda, Febrianda; Mhd. Azhali Siregar; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
Sighat ta'lik talak is an agreement made by a husband after the marriage contract, which gives the wife the right to file for divorce if the husband violates the agreed provisions. In the Islamic legal system in Indonesia, sighat ta'lik talak is recognized in the Compilation of Islamic Law (KHI) and several related regulations, but does not yet have a strong legal basis in Law Number 16 of 2019 concerning Marriage. As a result, sighat ta'lik talak is often viewed as a formality without a deep understanding of its legal implications. In practice, violation of sighat ta'lik talak does not immediately lead to divorce, but must be submitted to the Religious Court to obtain a legal decision. This study uses a normative legal method with a doctrinal-deductive approach and analysis of legal regulations related to sighat ta'lik talak. The results of the study indicate that sighat ta'lik talak has an important role in protecting the rights of wives, especially in cases of neglect of livelihood and domestic violence. However, there are still obstacles in its implementation, including the lack of public understanding and the absence of regulations governing the legal consequences for husbands who violate sighat ta'lik talak. Therefore, it is necessary to strengthen the position of sighat ta'lik talak in Indonesian positive law to be more effective in providing legal protection for wives. In addition, a revision of the sighat ta'lik talak clause to be more relevant to current social and economic conditions is also urgent.